1988
DOI: 10.1111/j.1752-1688.1988.tb03036.x
|View full text |Cite
|
Sign up to set email alerts
|

COLD‐SHOCK RESISTANCE TO LARGEMOUTH BASS, BLUEGILL, AND CHANNEL CATFISH1

Abstract: Juvenile specimens of largemouth bass, bluegill, and channel catfish were tested to determine their ability to withstand abrupt temperature decreases simulating the environmental impact from a sudden shutdown of a nuclear reactor during the winter. Temperature reductions were administered over 2‐hour and 24‐hour periods to assess the importance of the rate of temperature change and hence the mitigative value of having a holding pond with a one‐day retention time between the proposed cooling tower discharge and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Managing to prevent cold‐shock stress is very difficult as causal events tend to be temporally and spatially unpredictable. Currently, there are several mitigation measures that can be taken to reduce the risk of cold‐shock stress and mortality on fishes (Wilde, 1988; Nickel et al , 2004), but until more research can be conducted, management bodies that take a precautionary approach should consider rapid declines in temperature as a threat to fish species. Although a number of guidelines for protecting fish from deleterious temperature regimes have been proposed (Oliver & Fidler, 2001; US EPA, 2003), the majority of these guidelines fail to specifically consider cold shock.…”
Section: Management Considerationsmentioning
confidence: 99%
“…Managing to prevent cold‐shock stress is very difficult as causal events tend to be temporally and spatially unpredictable. Currently, there are several mitigation measures that can be taken to reduce the risk of cold‐shock stress and mortality on fishes (Wilde, 1988; Nickel et al , 2004), but until more research can be conducted, management bodies that take a precautionary approach should consider rapid declines in temperature as a threat to fish species. Although a number of guidelines for protecting fish from deleterious temperature regimes have been proposed (Oliver & Fidler, 2001; US EPA, 2003), the majority of these guidelines fail to specifically consider cold shock.…”
Section: Management Considerationsmentioning
confidence: 99%
“…HSPs have been found to repair and prevent damage from cellular stress associated with protein denaturation at high and low temperatures (Nakano and Iwama, 2002;Werner et al, 2005). However, HSPs expression is fluctuating at both stresses according to fish species (Werner et al, 2005;Wilde, 1988). Glutathione S-transferases (GST), one of the oxidative stress-related genes, its expression associated with different kinds of stressors (Almroth et al, 2015;Garcia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have repeatedly documented the attraction of fish to heated discharges during cold months (Benda and Proffitt 1973). In addition, numerous laboratory studies have been conducted to determine the effects of heat and cold shock on fish (e.g., Reutter and Herdendorf 1976;Wilde 1988). However, Sawyko and Smythe (1983) suggested that the application of laboratory results should not be generalized and related to field locations for which relevant parameters may be unknown.…”
mentioning
confidence: 99%